Isolation and Characterization of Uricase Produced from Chicken Liver - Wuryanti Handayani; Nasrul Amaliyatun Naja; Muhamad Kiki Afindia Joenata; Ratnadewi, Anak Agung Istri (Universitas Airlangga, 2022)
Uricase is an enzyme that degrades uric acid into allantoin. One of the uricase sources is obtained from chicken species (Gallus gallus domesticus) liver which are broiler and native chicken. This study aims to determine the maximum uricase activity in broiler and native chicken liver. The uricase activity was obtained by measuring the uric acid concentration as uricase substrate using spectrophotometric method and wavelength at 291 nm. Uricase isolation was carried out into extraction process, ammonium sulfate fractionation (0-60% saturation of ammonium sulfate), and dialysis. During isolation process, centrifugation speed was also optimized to obtain the maximum uricase crude extract and uricase activity. The molecular weight of uricase was also determined by SDS PAGE. The result showed that the highest uricase activity remained using centrifugation speed of 15,000 rpm. The optimum uricase fraction for broiler chicken liver was obtained at 20-40% saturation of ammonium sulfate with uricase activity was 1.854 x 10-2 U/mg, and the uricase fraction for native chicken liver was obtained at 40-60% saturation of ammonium sulfate with uricase activity was 2.496 x 10-2 U/mg. The optimum fraction for uricase production and isolation is carried out to the dialysis process. The optimum uricase activity of broiler chicken liver crude extract was 4.921 x 10-4 U/mg, the uricase fraction was 3.989 x 10-3 U/mg, and the dialysate was 5.120 x 10-3 U/mg. While the native chicken liver crude extract was 2.980 x 10-4 U/mg, the uricase fraction was1.415 x 10-2 U/mg, and the dialysate was 1.753 x 10-2 U/mg. The molecular weight of the uricase was around 35 kDA according to the SDS PAGE result.